The Effect of Singkil Leaves (Premna corymbosa) on Continuity and Increased Milk Production in Breastfeeding Mothers at UPT Puskesmas Tanjung Redeb - Farhany Diah Rahayu; Endah Wahyutri; Rahmawati Shoufiah (Formosa Journal of Science and Technology, 2023)
Efforts to achieve the goals of the Sustainable Development Goals (SDGs) start from infancy by providing Mother's Milk so that humans can live in a healthy and prosperous life. There are still many breastfeeding mothers who have less milk production and lack of innovation based on family medicinal plants to overcome the problem of lack of milk production in breastfeeding mothers using cassava leaves. This study aims to determine the effect of cassava leaves (Premna corymbosa) on the smooth production of breast milk in breastfeeding mothers at the UPT Puskesmas Tanjung Redeb. This type of research is comparative quantitative with a true-experiment research design using a pre-post-test without control group design. The bivariate test showed smooth milk production (sig 0.000; t-count 8.375) and increased milk production (p-value 0.004; t-count 3.161). So it can be concluded that there is a significant effect on cassava leaves (Premna corymbosa) on the smoothness and increase in milk production in breastfeeding mothers at the UPT Puskesmas Tanjung Redeb.